DIGITAL TECHNOLOGIES IN MUSIC EDUCATION - Raxmatova Nargiza Dolibaevna (World Scientific Research Journal, 2025)
Annotation: This article presents the importance of digital technologies in music education, multimedia lectures used in the lessons of musical and theoretical disciplines in the system of professional music education, methodological principles that should be followed when creating this form of lectures.